2008
DOI: 10.1128/aac.00456-08
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Various Definitions of Prior Antibiotic Exposure and Piperacillin-Tazobactam Resistance among Patients with Respiratory Tract Infections Caused by Pseudomonas aeruginosa

Abstract: Contemporary literature lacks a definition of prior antibiotic exposure which captures all patients at risk of developing piperacillin-tazobactam-resistant Pseudomonas aeruginosa (PTR-PA). The results indicated that individual antibiotics that are associated with PTR-PA differ depending on the definition of prior antibiotic exposure utilized. When the specific antibiotic used was replaced by the number of prior exposures, the number of exposures was the only variable associated with an increased risk of antibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…A previous Israeli case‐control report found that 82 multidrug‐resistant PA‐carrying patients were more often treated with prior broad‐spectrum antibiotics . In a study assessing different definitions of antibiotic exposure, ureidopenicillin resistance was associated with prior exposure to any antibiotics, depending on the cumulative burden of prior exposures . Our study is far larger than these previous analyses and presents patient‐unique data spanning two decades.…”
Section: Discussionmentioning
confidence: 85%
“…A previous Israeli case‐control report found that 82 multidrug‐resistant PA‐carrying patients were more often treated with prior broad‐spectrum antibiotics . In a study assessing different definitions of antibiotic exposure, ureidopenicillin resistance was associated with prior exposure to any antibiotics, depending on the cumulative burden of prior exposures . Our study is far larger than these previous analyses and presents patient‐unique data spanning two decades.…”
Section: Discussionmentioning
confidence: 85%
“…Similar to the previous studies in Turkey, we found that 44 of 120 P. aeruginosa strains (36.7%) strains were resistant to piperacillin-tazobactam. Different studies on resistant P. aeruginosa infections have shown that ICU stay is a major risk factor [ 26 28 ]. In the present study we classified our patients with respect to the type of ICU.…”
Section: Discussionmentioning
confidence: 99%
“…The use of TZP, MEM, and CIP within 30 days before isolation was significantly higher in the TZP-R Pa group. To date, studies have identified previous use of piperacillin-tazobactam, imipenem, aminoglycosides, vancomycin, and third-generation cephalosporins as independent risk factors [ 27 , 28 ]. Similar studies of hospital infections in the same settings have identified the use of broad spectrum cephalosporins, ciprofloxacin, and fluoroquinolones within 30 days before isolation as an independent risk factor [ 26 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Age, APACHE II score and SOFA score were introduced into the models as dichotomous variables, taking the median as the cutoff value, whereas colonization pressure was dichotomized by the highest observed value (95th percentile). In multivariate models predicting the acquisition of strains resistant to each antipseudomonal agent and multiple drugs, a cutoff of 72 hours was used to dichotomize antibiotic exposure because in previous studies it appeared to be the best time span for defining the minimal duration of exposure associated with resistance [ 39 , 40 ]. Variables with a P -value <0.3 in the univariate analysis were introduced into the multivariate model.…”
Section: Methodsmentioning
confidence: 99%